Does deprivation influence treatment outcome in physiotherapy?. (August 2014) - Lowe, Anna; Campbell, Lorna; Ramaswamy, Bhanu; Horobin, Hazel; McLean, Sionnadh
<x content-type="archive" xml:space="preserve">Abstract</x> Background: The relationship between deprivation status and health is well documented with less deprived populations experiencing lower rates of morbidity and mortality than those from more deprived groups. The mechanisms that link deprivation to health are multi-factorial and complex. The relationship between deprivation and health remains largely unexplored in physiotherapy management. Objectives: To systematically collate, appraise, and summarize primary studies that investigate the relationship between deprivation and treatment outcomes in physiotherapy. Methods: A systematic search of electronic databases was performed using a specified strategy. A three-phase screening process was used to identify relevant primary studies. Two independent reviewers selected the articles, rated quality, and extracted data. Meta-analysis was not performed due to diversity of conditions, interventions, and outcome measures used. Qualitative analysis was performed, and levels of evidence were generated using an established framework. Results: Three studies met the inclusion criteria; all were deemed of high quality. All three studies found that low socioeconomic status (SES) negatively influenced physiotherapy treatment outcomes. Conclusion: There is strong evidence to suggest that low SES negatively affects treatment outcomes in physiotherapy. This is in line with findings from other areas of medicine and allied health. The relationship appears to be complex and multifaceted. Key potential causal mechanisms are identified and explored with reference to existing literature. Further research is required to elucidate this complex relationship and to allow development of strategies that reduce the impact of deprivation on physiotherapy outcomes.